2021
DOI: 10.3389/fgene.2021.631340
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Landscape of Rare Autoinflammatory Disease Variants in Qatar and Middle Eastern Populations Through the Integration of Whole-Genome and Exome Datasets

Abstract: Rare monogenic autoinflammatory diseases are a group of recurrent inflammatory genetic disorders caused due to genetic variants in over 37 genes. While a number of these disorders have been identified and reported in Middle Eastern populations, the carrier frequency of these genetic variants in the Middle Eastern population is not known. The availability of whole-genome and exome datasets of over 1,000 individuals from Qatar persuaded us to explore the genetic epidemiology of rare autoinflammatory genetic vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
3
1
Order By: Relevance
“…In contrast with similar approaches towards understanding the genetic epidemiology of autoinflammatory diseases in other populations, three of the causal variants in the present analysis overlapped with our previous analysis of the Middle Eastern population [ 21 ]. Compared to the variant frequencies in the global populations, a number of disease alleles have frequencies in Indian population higher than global datasets including rs116107386, rs78635798, rs104895364, rs28934897, rs104895492, rs200930463, and rs202134424.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In contrast with similar approaches towards understanding the genetic epidemiology of autoinflammatory diseases in other populations, three of the causal variants in the present analysis overlapped with our previous analysis of the Middle Eastern population [ 21 ]. Compared to the variant frequencies in the global populations, a number of disease alleles have frequencies in Indian population higher than global datasets including rs116107386, rs78635798, rs104895364, rs28934897, rs104895492, rs200930463, and rs202134424.…”
Section: Discussioncontrasting
confidence: 80%
“…Also, Thaventhiran et al has identified eight SVs by performing the WGS of 1318 patients affected with PID, that could be missed using the WES [ 20 ]. WGS has also been implemented at the population scale for autoinflammatory disorders to comprehend the genetic epidemiology of the Qatari population [ 21 ]. Even though India is a hotspot for the genetic disorder due to the prevalent practice of endogamy and consanguineous marriages, migration, and large population size, the genetic epidemiology of autoinflammatory disorders in the country has not been studied much except for a few reports [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autoinflammatory diseases are genetically based disorders associated with a dysregulation of the innate immune system, resulting in uncontrolled inflammation [ 17 ]. Variants associated with AIDs are included in the 2022 classification of human inborn errors of immunity [ 18 ], many of them caused by monogenic germline or somatic mutations, and include 485 distinct disorders categorized into autoimmune, autoinflammatory, allergic, and malignant phenotypes [ 19 ]. The most well-known AID is familial Mediterranean fever (FMF), which is caused by variants in the MEFV gene [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, similar associations between PYCARD variations and altered gene expression have been observed in various cancers, including lung cancer [ 22 ], breast cancer [ 23 ], schwannoma tumor [ 4 ], prostate cancer [ 24 ], and pancreatic ductal adenocarcinoma [ 10 ]. Polymorphisms in the PYCARD gene appear to be associated with slightly higher frequencies of T and G allele changes than those found in Asians and the global population of allele frequency based on the gnomAD [ 25 ]. The study identified specific PYCARD gene variations (high T and G allele frequencies) associated with an increased risk of periodontal and cardiovascular diseases in the Iraqi population.…”
Section: Discussionmentioning
confidence: 99%